2007
DOI: 10.1016/j.drudis.2006.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Targeting structural flexibility in HIV-1 protease inhibitor binding

Abstract: SummaryHIV-1 protease remains an important AIDS drug target. Even though it has been known that ligand binding induces large conformational changes in the protease, the dynamic aspects of binding have been largely ignored. Several computational models describing protease dynamics have been reported recently. These have reproduced experimental observations, and also explained how ligands gain access to the binding site through dynamic behavior of the protease. Specifically, the transitions between three differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
105
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 63 publications
(72 reference statements)
2
105
0
1
Order By: Relevance
“…1A), which are seen to close over the substrate or substrate-derived inhibitor in the crystal state (8)(9)(10)(11). The conventional view is that the role of the flaps is to provide a gating mechanism for substrate binding and for product release, and to help to orient the substrate within the enzyme-substrate complex in a conformation suitable for catalysis (2)(3)(4)(5)(6)(7). In the work reported here, we have reinvestigated the role of the HIV-1 protease flaps in enzyme catalysis by employing advanced biophysical methods in conjunction with a series of unique analogue enzymes prepared by total chemical synthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1A), which are seen to close over the substrate or substrate-derived inhibitor in the crystal state (8)(9)(10)(11). The conventional view is that the role of the flaps is to provide a gating mechanism for substrate binding and for product release, and to help to orient the substrate within the enzyme-substrate complex in a conformation suitable for catalysis (2)(3)(4)(5)(6)(7). In the work reported here, we have reinvestigated the role of the HIV-1 protease flaps in enzyme catalysis by employing advanced biophysical methods in conjunction with a series of unique analogue enzymes prepared by total chemical synthesis.…”
mentioning
confidence: 99%
“…NMR studies of the HIV-1 protease have identified regions of the protein molecule with enhanced mobility (2,3), and attempts have been made with the help of molecular dynamics (MD) simulations to utilize knowledge of the dynamic properties of the HIV-1 protease protein molecule for improved drug design and to rationalize drug resistant mutations (4)(5)(6)(7). Particularly important are two highly mobile regions in the HIV-1 protease molecule, the pair of so-called "flaps" (Fig.…”
mentioning
confidence: 99%
“…Currently there are several 3D crystal structures of free HIV-1 protease or complexed with substrate and inhibitors reported in the literature and available in Protein Data Bank (Zoete et al, 2002;Hornak and Simmerling, 2007;Verkhivker et al 2008;Cunha et al, 2009;Meredith et al, 2010). HIV-protease complexed with saquinavir is shown in Figure 3 where some residues important for this inhibitor binding are highlighted: Arg8, Asp25, Thr26, Gly27, Asp29, Asp30, and Gly48 in a-chain and Asp25, Thr26, and Gly27 in b-chain (Figure 3).…”
Section: A Recent Aspartyl Family Member: Hiv Proteasementioning
confidence: 95%
“…36 A molécula desta classe de fármacos que estava em fase clínica mais avançada era o brecanavir (30) (Figura 16), 37 porém seu estudo foi descontinuado em dezembro de 2006, devido a problemas na dosagem da formulação.…”
Section: Outros Alvos Terapêuticosunclassified